Illustration of K Mean Clustering Algorithm for Analysing Laptop Utilization Dataset - Praba, V. Lakshmi; Banu, M.A. Saira (International Journal of Computer Sciences and Engineering, 2025)
Laptops finds wide application in different fields by different users. School and College students are provided with Laptops freely distributed by the Government. These laptops are used by the students for various purposes like academic, programming, writing, editing documents, etc. To carry out the task of analysing the Laptop utilization characteristics, data has been collected from college students by supplying questionnaires. This paper examines student‘s perceptions related to the usage of laptop by analyzing its utilization characteristics using Simple K-Means clustering algorithm.